Diversity and putative metabolic function of prokaryotic communities in tank bromeliads along an elevation gradient in tropical Mexico - Aguilar-Cruz, Yonatan; Milke, Felix; Leinberger, Janina; Poehlein, Anja; Zotz, Gerhard; Brinkhoff, Thorsten (Frontiers in Microbiology, 2022)
Tank bromeliads are unique canopy microhabitats that offer freshwater and organic nutrient-rich substrates in the Neotropics. In them it is possible to thoroughly characterize environmental factors and species composition of terrestrial and aquatic biota. Therefore, these plants have been used as natural models to study how communities are distributed and assembled. Here we used amplicon sequencing of the 16S rRNA gene and their functional annotations to study the diversity and metabolic potential of prokaryotic communities in tank bromeliads in five different forests along an elevation gradient in tropical Mexico. Furthermore, we analyzed the effects of vegetation type and environmental factors inside the tanks on prokaryotic composition. We found a high prokaryotic diversity in tank bromeliads along the elevation gradient. Prokaryotes commonly observed in acidic environments rich in organic carbon, and the potential pathogen Pasteurella multocida, were present in all samples, but few amplicon sequence variants were shared between forests. The prokaryotic composition was affected by forest type, and comparisons against null models suggest that it was shaped by non-neutral processes. Furthermore, prokaryotic community changes significantly covaried with tank water temperature, pH, and inorganic carbon. We found a high diversity of putative metabolic groups dominated by chemoheterotrophs and fermenters, but taxonomic groups involved in nitrogen and sulfur cycling were also present in all samples. These results suggest that tank bromeliads promote taxonomic and metabolic diversity of the prokaryotic community at a local and regional scale and play an important role in the biogeochemistry of forest canopies in the Neotropics.